Market Entry of Biosimilar Low-Molecular-Weight Heparins in Europe: Opportunities and Challenges - Simoens, Steven; Huys, Isabelle (Seminars in Thrombosis and Hemostasis, 2013)
This article examines the market entry of biosimilar low-molecular-weight heparins (LMWHs) in Europe by focusing on regulatory requirements, pricing, reimbursement, prescribing, and dispensing. The window for biosimilar LMWHs to enter the market is narrow on the supply side because of several factors. These include (1) regulatory requirements, including a quality dossier, clinical and nonclinical studies, pharmacodynamic and pharmacokinetic studies, immunogenicity studies, and a comparability exercise (but a reduction in clinical data requirements might be plausible in some cases); (2) prices of originator LMWHs are lower than those of other biologic products; (3) European prices of originator LMWHs are lower than those observed in the rest of the world; (4) research and development and manufacturing costs are substantial; (5) costs of active pharmaceutical ingredients have increased following the heparin contamination crisis; and (6) biosimilar LMWHs may be subjected to generic medicine pricing regulations. Furthermore, there are limited opportunities for biosimilar LMWHs on the demand side. This is because, although LMWHs have a large market volume in Europe, demand-side incentives for biosimilar LMWHs are largely absent, and the questions about interchangeability and substitution between originator and biosimilar LMWHs have yet to be fully resolved.
Keywords: market entry; low-molecular-weight heparin; biosimilar